Dewatering of source-separated human urine for nitrogen recovery by membrane distillation - Tun, Lat Lat; Jeong, Dawoon; Jeong, Seongpil; Cho, Kyungjin; Lee, Seockheon; Bae, Hyokwan (Elsevier BV, 2016)
The nitrogen content of a synthetic ammonia wastewater was concentrated using direct contact membrane distillation (DCMD). The ratio of transferred ammonia to water (i.e., specific ammonia transfer: SAT) was controlled by operational conditions. With 20 degrees C on the permeate side, and a high temperature of 70 degrees C on the feed side, the process exhibited low SAT values for PTFE/PP (PTF045LD0A), PTFE/PP (TF-450), and PVDF (HVHP-14250) membranes. This was because the increase in water flux ( >24 L/m(2) h) was greater than that of ammonia transfer. A positive relationship between SAT and free ammonia concentration was identified under different total ammoniacal nitrogen concentration and pH. The acidification pretreatment to pH 5 led to further reduction in the SAT value (as low as 6.91 x 10(-5) g-N/g-H2O). As a practical application, the dewatering process of source-separated human urine by DCMD required an additional filtration step to prevent fouling, but the filtration had an insignificant effect on the SAT. For the acidified and filtered source-separated human urine, total ammoniacal nitrogen was successfully concentrated with a low SAT value ( < 2.06 x 10(-3) g-N/g-H2O). (C) 2016 Elsevier B.V. All rights reserved.